Peranan Guru Al-Quran Dalam Mengatasi Kesulitan Anak Dalam Membaca Al-Quran (Metode Iqro) Di Tadika Nurulhidayah Budi Patani Selatan Thailand - Nurhayatee Yusoh; Hotni Sari Harahap; Ade Rahman Matondang (Journal of Innovative and Creativity, 2025)
This research discusses the Role Of Al-Quran Teachers In Overcoming Children's Difficulties In Reading The Al-Quran (Iqro Method) At Tadika Nurulhidayah Budi Patani South Thailand, with the main problem: What is the role of Al-Quran teachers in overcoming children's difficulties in reading the Al-Qur'an at Tadika Nurulhidayah school Budi Yaring South Thailand 2023/2024 academic year. Through the principal, Al-Quran teacher, and students of the Tadika Nurulhidayah Budi South Yaring school, Thailand. Used as a data source to obtain a portrait of the teacher's role in overcoming difficulties in reading the Koran. This type of research is field research and the approach used is a qualitative approach. Data collection uses interviews, observation and documentation. The data validity method uses triangulation of methods and sources. Data analysis uses descriptive analysis. The results of the study show that: The role of teachers in overcoming children's difficulties in reading the Qur'an at the Tadika Nurulhidayah Budi Yaring Selatan Thailand school for students is considered optimal. With the many efforts that have been made, students' ability to read the Qur'an should be... getting better. Teachers have made many efforts to help their students who are still having difficulty reading the Qur'an, but some of the students have no interest in learning. They know that their reading ability is still lacking, but their desire to learn is which does not exist yet. Until now, the Quran teachers at Tadika Nurulhidayah Budi Yaring Selatan Thailand school are still trying to develop students' interest in learning to read the Quran.